2009
DOI: 10.1038/ijo.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in midlife and risk of dementia: a 40-year follow-up study

Abstract: Objective: This study examines whether overweight in midlife increases dementia risk later in life. Methods: In 1963 body mass index was assessed in 1152 participants of The Swedish Twin Registry, at the age of 45-65 years. These participants were later screened for dementia in a prospective study with up to 40 years follow-up. A total of 312 participants were diagnosed with dementia. Results: Logistic regression analyses adjusted for demographic factors, smoking and alcohol habits, indicated that men and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 34 publications
2
90
0
1
Order By: Relevance
“…A growing body of evidence suggests that a high level of adiposity is associated with cognitive decline and dementia 10,26,27 ; however, the relation between BMI and dementia among people aged over 65 is controversial. [28][29][30] Several population-based studies have reported an effect of obesity at middle age on dementia risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that a high level of adiposity is associated with cognitive decline and dementia 10,26,27 ; however, the relation between BMI and dementia among people aged over 65 is controversial. [28][29][30] Several population-based studies have reported an effect of obesity at middle age on dementia risk.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the last decade, many population-based longitudinal studies have evaluated the relationship between adiposity and dementia. Several reports have shown that midlife obesity increases the risk of dementia in late life [3][4][5][6][7][8][9][10] ; however, the effect of midlife overweight on dementia is controversial. 3,5,7,9 Currently, the prevalence of overweight and obesity is over 50% among adults in the United States and Europe.…”
mentioning
confidence: 99%
“…However, as with other diseases, the relationship between BMI and T2DM risk also varies by ethnicity (314,499). Other diseases associated with obesity include various types of cancer (70,112,201,433), ischemic stroke (358,501,579), heart failure (245), dementia (202), venous thrombosis (7), gallstones (489), gastroesophageal reflux disease (386), renal disease (145), sleep apnea (570), and osteoarthritis (83). Particularly pertinent to this review, maternal obesity is associated with gestational complications and adverse fetal and neonatal health outcomes (348,513).…”
Section: B Prevalence and Associated Morbidity And Mortality Of Obesitymentioning
confidence: 99%
“…A recent study showed that the hypothalamus of obese humans and of experimental models of obesity presents signs of inflammation and dysfunction that precede the installation of increased adiposity and T2D (15). Obesity, often associated with consumption of diets that are high in fat, has also been proposed to increase the risk of dementia and AD later in life (16)(17)(18). Epidemiologic studies further suggest that diets high in saturated fats during midlife are a risk factor for development of AD later in life (19,20).…”
mentioning
confidence: 99%